Serbia and Montenegro : Third Review Under the Extended Arrangement and Requests for Waiver of a Performance Criterion and Rephasing of Purchases. (IMF Staff Country Reports; Country Report ;, 2004)
This paper examines Serbia and Montenegro's Third Review Under the Extended Arrangement and Requests for Waiver of Performance Criterion. Serbia and Montenegro's recent economic performance has been mixed, combining excellent progress in some areas with an uncomfortably large current account deficit and modest growth in output and exports from low levels. The envisaged tightening of fiscal policy is broadly appropriate-albeit overly reliant on revenue measures. Achieving the fiscal deficit target will help narrow the current account deficit and place the fiscal and external accounts on sustainable paths.